Method for modifying carbon fibers by using multi-dimensional nanoparticles and application of carbon fibers in CF / PEEK composite material
Through the method of modifying carbon fibers by multi-dimensional nanoparticles, the problem of insufficient interface bonding force of CF/PEEK composite materials is solved, and a high-strength and excellent electromagnetic shielding performance CF/PEEK composite material is achieved, avoiding the disadvantages of using toxic solvents and damaging fiber strength.
Patent Information
- Application Number
- CN202411724319.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The interface bonding force between carbon fiber (CF) and polyether ether ketone (PEEK) is weak, affecting the overall performance of CF/PEEK composite materials. The existing modification methods have disadvantages such as damaging the fiber strength, time-consuming and using toxic solvents.
Through the multi-dimensional nanoparticle modification method of carbon fiber, cationic polyelectrolyte PEI with rich amino groups interacts electrostatically with the oxygen functional group on the surface of CF, adsorbing cationic groups to make the fiber positively charged, and depositing MXene nanosheets with positive and negative charge properties with modified PEI-CB nanoparticles on the fiber surface, avoiding the use of organic solvents and enhancing the physical interlocking effect between the activity of the fiber surface and the resin.
The bonding strength between carbon fiber and polyether ether ketone is effectively improved. The bending strength of the modified composite material can reach 781.54MPa, the interlayer shear strength is 67.1MPa, and the electromagnetic shielding performance in the X-band reaches 29.28dB, which has excellent comprehensive performance.
Smart Images

Figure CN119553504A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of carbon fiber modification and CF / PEEK composite material preparation, and specifically relates to a method for modifying carbon fiber with multidimensional nanoparticles and an application in CF / PEEK composite materials. Background Art
[0002] Carbon fiber reinforced polymer matrix composites have excellent physical and chemical properties, including high specific strength, specific stiffness, light weight, strong corrosion resistance, excellent thermal stability and easy molding. They have been widely used in many fields such as aerospace, national defense, military, transportation, etc. Among the commonly used high-performance thermoplastic resin matrices, polyetheretherketone (PEEK) has the best comprehensive performance. It is a semi-crystalline polymer that contains benzene rings, ether bonds and ketone bonds in its structure.
[0003] However, the surface of carbon fiber (CF) is smooth, chemically inert and has low surface energy. The inertness of PEEK causes the interfacial bonding force between the fiber and the matrix to be weak, which affects the overall performance of CF / PEEK composites. Therefore, it is necessary to modify the surface of carbon fiber. In recent years, many carbon fiber surface modification methods have been developed, mainly by improving the polarity, surface roughness and surface energy of the fiber to enhance the interfacial properties of carbon fiber composites. However, most modification methods, while improving the interfacial properties, will have the disadvantages of damaging the strength of the fiber body, consuming time, and using toxic solvents. Therefore, it is crucial to study a simple and environmentally friendly CF surface modification method to solve the interface problems of CF / PEEK composites, improve the overall mechanical properties of the composite material and give full play to its functionality. Summary of the invention
[0004] The purpose of the present invention is to solve the interface problem of CF / PEEK composite materials and improve the overall mechanical properties of the composite materials, and to provide a method for modifying carbon fibers with multidimensional nanoparticles and an application in CF / PEEK composite materials.
[0005] One of the purposes of the present invention is to provide a method for modifying carbon fiber with multidimensional nanoparticles, the method being carried out according to the following steps:
[0006] S1: Activating the surface oxygen-containing functional groups of the desized CF fabric, and then immersing it in an aqueous solution of polyethyleneimine (PEI) under heating conditions to obtain PEI-modified CF;
[0007] S2: immerse the PEI-modified CF in a MXene suspension and dry it at room temperature to obtain a MXene-modified CF, which is recorded as MCF;
[0008] S3: adding conductive carbon black (CB) and PEI to deionized water, magnetically stirring under heating conditions, then ultrasonically treating, filtering, washing, low-temperature drying, and grinding to obtain PEI-modified CB;
[0009] S4: Dispersing the PEI-modified CB in deionized water to obtain a dispersion, then immersing the MCF in the dispersion, and drying at low temperature to obtain a carbon fiber modified with multidimensional nanoparticles.
[0010] It is further defined that the desizing process of the CF fabric in S1 is: Soxhlet extraction in acetone under heating conditions, followed by washing and drying.
[0011] It is further defined that in S1, the surface oxygen-containing functional groups are activated by immersing in a Michaelis acid / ethanol solution.
[0012] It is further defined that the concentration of the PEI aqueous solution in S1 is 0.5-1.5 g / L.
[0013] It is further defined that the soaking temperature in S1 is 40-60° C. and the soaking time is 0.5-1.5 h.
[0014] It is further defined that the concentration of MXene suspension in S2 is 0.5-1.5 g / L.
[0015] It is further defined that the immersion in S2 is 20-40 minutes.
[0016] It is further defined that the mass ratio of CB to PEI in S3 is (0.5-1.5):1.
[0017] It is further defined that the ratio of PEI to deionized water in S3 is 1 g: (80-120) mL.
[0018] It is further defined that the magnetic stirring temperature in S3 is 50-70°C and the time is 3-5h.
[0019] Further defined, the ultrasonic treatment in S3 is 3-5 h.
[0020] It is further defined that the low temperature drying temperature in S3 is 25-40°C.
[0021] It is further defined that the concentration of the dispersion in S4 is 1-5 g / L.
[0022] Further defined, soaking in S4 for 20-40 minutes.
[0023] It is further defined that the low temperature drying temperature in S4 is 25-40°C.
[0024] The second object of the present invention is to provide a multi-dimensional nanoparticle modified carbon fiber prepared by the above method.
[0025] The third object of the present invention is to provide a CF / PEEK composite material based on the above-mentioned multi-dimensional nanoparticle modified carbon fiber.
[0026] A fourth object of the present invention is to provide a method for preparing a CF / PEEK composite material based on the multidimensional nanoparticle-modified carbon fiber, the method being carried out according to the following steps:
[0027] The multi-dimensional nanoparticle modified carbon fiber and PEEK film are alternately layered and then hot pressed.
[0028] It is further defined that the volume ratio of the multi-dimensional nanoparticle modified carbon fiber to the PEEK film is (7-5):4.
[0029] The hot pressing conditions are further defined as follows: preheating at 150-250°C for 20-40 min under 4-6 MPa conditions, heating to 350-400°C and keeping warm for 20-40 min, cooling to 250-350°C and keeping warm for 20-40 min, and cooling to room temperature.
[0030] A fifth object of the present invention is to provide an application of the above-mentioned CF / PEEK composite material in the field of electromagnetic shielding.
[0031] Compared with the prior art, the present invention has the following significant effects:
[0032] (1) In order to solve the interface problem between CF and PEEK, the present invention proposes a simple and environmentally friendly method for electrostatic assembly of fiber surface. First, cationic polyelectrolytes with rich amino groups are used to interact electrostatically with oxygen functional groups on ACFs. The surface of CF carries cationic charges. Due to the branched molecular structure of polyelectrolyte PEI, NH3 can be decomposed in water. + 、NRH2 + and NR2H + Cationic groups such as PEI and PEI-CB can be adsorbed on the surface of CF under electrostatic interaction to make the fiber positively charged. Therefore, PEI can act as a bridging part to connect ACF with the self-assembled stacking layer. Then, MXene nanosheets with positive and negative charge properties and modified PEI-CB nanoparticles are deposited on the fiber surface in sequence, avoiding the use of organic solvents and the problem of damaging the strength of the body, while improving the activity of the fiber surface and the physical interlocking effect between the fiber and the resin, so as to improve the interface bonding between the fiber and the matrix, thereby improving its mechanical properties and electromagnetic shielding properties, and preparing a composite material with integrated structure and function.
[0033] (2) The present invention proposes a simple and feasible green assembly method to deposit nanomaterials of different dimensions on the CF surface, which effectively improves the bonding strength between carbon fiber and polyetheretherketone. The bending strength of the modified composite material can reach 781.54MPa, and the interlaminar shear strength is 67.1MPa. At the same time, the electromagnetic shielding performance in the X-band reaches 29.28dB, which has excellent comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The morphology SEM images of MXene, CB and PEI-CB used in the embodiments of the present invention; wherein (a, b) represent MXene, (c, d) represent CB, and (e, f) represent PEI-CB;
[0035] Figure 2 The Raman spectra of the raw materials used in the embodiments of the present invention and the products obtained in each step;
[0036] Figure 3 The SEM images of the morphology of the CF modified with MXene / PEI-CB in the embodiment of the present invention and the unmodified carbon fiber in the comparative example; a) represents the comparative example, and b) represents the embodiment;
[0037] Figure 4 A comparison chart of the flexural strength and interlaminar shear test of the carbon fiber reinforced polyetheretherketone composite material prepared in the embodiment of the present invention and the comparative example;
[0038] Figure 5 This is a comparison chart of the electromagnetic shielding performance of the carbon fiber reinforced polyetheretherketone composite materials prepared in the examples of the present invention and the comparative examples in the X-band. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0040] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0041] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0042] The "one embodiment" or "embodiment" referred to in the following embodiments refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0043] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.
[0044] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0045] The endpoints and any values of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.
[0046] Example:
[0047] The preparation method of the CF / PEEK composite material based on multi-dimensional nanoparticle modified carbon fiber in this embodiment is carried out according to the following steps:
[0048] (1) First, commercial CF (CCF) fabric was extracted in acetone at 80°C for 24 h by Soxhlet extraction to remove commercial sizing agents and impurities on the surface. After washing with deionized water, it was dried in an oven at 80°C for 24 h to obtain desized CF fabric (BCF). BCF was placed in a 1.5 g / 100 mL Michaelis acid / ethanol solution (temperature 30°C) and soaked for 2 h, then washed with ethanol to remove unreacted Michaelis acid, and then dried at 80°C for 24 h to obtain activated CFs (ACFs) with carboxyl and hydroxyl groups on the surface.
[0049] Then, the ACFs were immersed in a PEI aqueous solution with a concentration of 1 mg / mL at 50 °C for 1 h, and then washed with deionized water and dried at room temperature overnight to obtain PEI-modified CFs.
[0050] (2) The purchased MXene with a concentration of 5 mg / mL was diluted to 1 mg / mL with deionized water and then ultrasonicated for 30 min to obtain a uniformly dispersed MXene suspension.
[0051] Then the PEI-modified CF was immersed in the MXene suspension for 30 min and dried in an oven at room temperature overnight to obtain a MXene-modified sample named MCF.
[0052] (3) 1 g of conductive carbon black (CB) and 1 g of polyethyleneimine (PEI) were added to 100 mL of deionized water, and the mixed solution was then magnetically stirred at 60 ° C for 4 h, and then reacted under ultrasonic conditions for 4 h. The suspension after the reaction was vacuum filtered with a 0.45 μm polyvinylidene fluoride filter membrane, and then the filtrate was washed with deionized water to remove the unreacted polyethyleneimine. The washed polyethyleneimine-modified carbon black (PEI-CB) was dried at 40 ° C in a vacuum oven and ground for later use.
[0053] (4) First, PEI-CB was dispersed in deionized water to prepare a suspension with a concentration of 3 mg / mL and then sonicated for 2 h.
[0054] Then, the MCF was immersed in the PEI-CB suspension for 30 min and dried at 40°C to obtain a multidimensional nanoparticle-modified carbon fiber cloth, which was recorded as MC3-CF.
[0055] The MXene (a, b), CB (c, d), and PEI-CB (e, f) were characterized by SEM microstructures, as shown in Figure 1The microscopic morphology of MXene is a two-dimensional nanosheet structure, while PEI-CB and CB are both spherical and have obvious agglomeration. The unique layered structure and the synergistic effect of nanoparticles can effectively fill the grooves on the surface of carbon fiber, increase the roughness of the fiber, and thus enhance the mechanical interlocking effect between the fiber and the resin matrix.
[0056] Raman spectroscopy tests were performed on MXene, PEI-CB, desized CF fabric (BCF), CF modified with only MXene (MCF), and CF modified with MXene and PEI-CB (MC3-CF). The results are shown in Figure 2. Figure 2 As shown, the three characteristic peaks of MXene are located at 201.5 cm - 1. 384.6cm - 1 and 623cm - 1, these peaks also appear in the Raman spectra of MCF and MC3-CF. The 2D characteristic peak of PEI-CB (2677cm -1 ) appeared in the spectrum of MC3-CF. These results confirmed that MXene and PEI-CB had been successfully deposited on the surface of CFs.
[0057] (5) The PEEK film was cleaned with ethanol under ultrasonic conditions and then dried in an oven at 80°C for 24 hours. The carbon fiber cloth modified with multidimensional nanoparticles and the PEEK film were alternately layered, wherein 8 layers of the carbon fiber cloth modified with multidimensional nanoparticles and 9 layers of the PEEK film (volume ratio 6:4), and then hot-pressed, specifically, preheated at 200°C for 30 minutes under 5MPa, then heated to 370°C and kept warm for 30 minutes, then cooled to 300°C and kept warm for 30 minutes, and cooled to room temperature to obtain a modified CF / PEEK composite material.
[0058] Comparative Example:
[0059] First, the commercial CF (CCF) fabric was extracted in acetone at 80 °C for 24 h by Soxhlet extraction to remove the commercial sizing agent and impurities on the surface. After washing with deionized water, it was dried in an oven at 80 °C for 24 h to obtain the desized CF fabric (BCF).
[0060] The PEEK film was cleaned with ethanol under ultrasonic conditions and dried in an oven at 80°C for 24 hours. The BCF woven cloth and the PEEK film were alternately layered, with 8 layers of BCF woven cloth and 9 layers of PEEK film (volume ratio 6:4), and then hot-pressed, specifically, preheated at 200°C for 30 minutes under 5MPa, then heated to 370°C and kept warm for 30 minutes, then cooled to 300°C and kept warm for 30 minutes, and cooled to room temperature to obtain a CF / PEEK composite material.
[0061] The unmodified carbon fiber (comparative example) and the modified carbon fiber (example) were characterized by SEM. Figure 3 As shown in the figure, the surface of the unmodified carbon fiber has obvious grooves. After modification, MXene nanosheets and PEI-CB nanoparticles are evenly deposited on the surface, and the fiber surface becomes obviously rough, which is conducive to improving the mechanical interlocking effect of the fiber and the resin matrix.
[0062] The carbon fiber reinforced polyetheretherketone composite materials prepared in the examples of the present invention and the comparative examples were tested for flexural strength and interlaminar shear strength according to ASTM D7264 and ASTM D2344, respectively. The results are as follows: Figure 4 The results show that the flexural strength of the modified composite material can reach 781.54MPa and the interlaminar shear strength is 67.1MPa.
[0063] The electromagnetic shielding performance of the carbon fiber reinforced polyetheretherketone composite materials prepared in the examples and comparative examples of the present invention was tested in the X-band. The results are as follows: Figure 5 The results show that the electromagnetic shielding performance of the carbon fiber reinforced polyetheretherketone composite material prepared in the embodiment of the present invention in the X-band reaches 29.28dB.
[0064] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for modifying carbon fiber with multidimensional nanoparticles, characterized in that: The method: S1: Activating the surface oxygen-containing functional groups of the desized CF fabric, and then immersing it in a PEI aqueous solution under heating conditions to obtain PEI-modified CF; S2: immerse the PEI-modified CF in a MXene suspension and dry it at room temperature to obtain a MXene-modified CF, which is recorded as MCF; S3: adding CB and PEI to deionized water, magnetically stirring under heating conditions, then ultrasonically treating, filtering, washing, low-temperature drying, and grinding to obtain PEI-modified CB; S4: Dispersing the PEI-modified CB in deionized water to obtain a dispersion, then immersing the MCF in the dispersion, and drying at low temperature to obtain a carbon fiber modified with multidimensional nanoparticles.
2. The method according to claim 1, characterized in that Desizing process of CF fabric in S1: Soxhlet extraction is carried out in acetone under heating conditions, followed by water washing and drying, and surface oxygen-containing functional groups are activated by immersion in Michaelis acid / ethanol solution. The concentration of PEI aqueous solution is 0.5-1.5 g / L, the immersion temperature is 40-60°C, and the time is 0.5-1.5 h.
3. The method according to claim 1, characterized in that The concentration of MXene suspension in S2 is 0.5-1.5 g / L, and the immersion time is 20-40 min.
4. The method according to claim 1, characterized in that The mass ratio of CB to PEI in S3 is (0.5-1.5):1, the ratio of PEI to deionized water is 1 g: (80-120) mL, the magnetic stirring temperature is 50-70°C, the time is 3-5 h, and the ultrasonic treatment is 3-5 h.
5. The method according to claim 1, characterized in that: The concentration of the dispersion in S4 is 1-5g / L, and the soaking time is 20-40min.
6. Multidimensional nanoparticle-modified carbon fiber prepared by the method described in any one of claims 1 to 5.
7. A CF / PEEK composite material based on the multidimensional nanoparticle-modified carbon fiber according to claim 6.
8. The method for preparing the CF / PEEK composite material according to claim 7, characterized in that: The method: The multi-dimensional nanoparticle modified carbon fiber and PEEK film are alternately layered and then hot pressed.
9. The method according to claim 8, characterized in that The volume ratio of multi-dimensional nanoparticle modified carbon fiber to PEEK film is (7-5):
4. The hot pressing conditions are: preheat at 150-250°C for 20-40min under 4-6MPa conditions, heat to 350-400°C and keep warm for 20-40min, cool to 250-350°C and keep warm for 20-40min, and cool to room temperature.
10. Application of the CF / PEEK composite material according to claim 7 in the field of electromagnetic shielding.
Citation Information
Patent Citations
MXene graphene synergistically reinforced high-content carbon fiber reinforced PEEK-based composite material and preparation method thereof
CN114591593A
Long fiber reinforced polyether-ether-ketone composite material and preparation method thereof
CN116376220A
MXene modified carbon fiber non-woven felt with multi-layer structure and preparation method of MXene modified carbon fiber non-woven felt
CN117947633A
Coarse aggregate ultra-high performance concrete with enhanced bending resistance and tensile strength and preparation method of coarse aggregate ultra-high performance concrete
CN118908664A